Ibsen and the Irish Revival - Malone, Irina Ruppo. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
Ibsen and the Irish Revival examines Henrik Ibsen's influence on the Irish Revival and the reception of his plays in turn-of-the-twentieth-century Dublin. It highlights the international dimension of the Irish Literary Revival and offers new perspectives on W.B. Yeats, J.M. Synge, Lennox Robinson, James Joyce, George Moore and Sean O'Casey.